2014
DOI: 10.1364/oe.22.006422
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium and thermal effects in mode-locked VECSELs

Abstract: Ultrafast femtosecond timescale dynamics in Vertical External Cavity Surface Emitting Lasers (VECSELs) have recently been employed to achieve record average power and duration mode-locked pulses by employing different types of saturable absorbers and Kerr Lens elements. Microscopic many-body dynamics are expected to dominate when attempting to push pulse durations below 100 fs. We present a preliminary microscopic simulation of ultrafast mode-locking in order to expose the role of hot carrier distributions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Significant attention has also been devoted to the so-called 'self-mode-locking' that was first reported by Chen et al in 2011 [375]. In these cases, the physical mechanism for the saturable absorption has been credited to a possible Kerr effect in the VECSEL gain material [376], but several reports have been published on the topic that both support and contradict self-mode-locking [207,211,307,[377][378][379][380][381]. Most notably, Quarterman et al [207] measured a sufficiently large Kerr effect in a VECSEL structure to support Kerr-lens mode locking.…”
Section: Mode-locking Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant attention has also been devoted to the so-called 'self-mode-locking' that was first reported by Chen et al in 2011 [375]. In these cases, the physical mechanism for the saturable absorption has been credited to a possible Kerr effect in the VECSEL gain material [376], but several reports have been published on the topic that both support and contradict self-mode-locking [207,211,307,[377][378][379][380][381]. Most notably, Quarterman et al [207] measured a sufficiently large Kerr effect in a VECSEL structure to support Kerr-lens mode locking.…”
Section: Mode-locking Mechanismmentioning
confidence: 99%
“…Again, it was found that measurable nonlinear lensing exists in VECSELs. However, whether this nonlinear lensing is strong enough to cause stable mode-locking is still under consideration [208,210,211].…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another modelocking mechanism reported recently is the so-called self-mode-locked VECSEL or the KLM-VECSEL [103][104][105][106] . No apparent saturable absorber is used in these laser cavities, and a hard aperture is inserted in front of the OC or highly reflective end mirror.…”
Section: Device Principle Vertical External-cavity Surface-emitting Lmentioning
confidence: 99%
“…4,5 Recently, there have been reports of SDLs operating in a pulsed regime without a saturable absorber in the cavity, so called self-mode-locking (SML). [6][7][8][9][10][11][12][13][14][15] It has been suggested that Kerr lensing in the gain medium 7,8 or saturable absorption in unpumped quantum wells (QWs) causes the observed pulsation. 6 However, there has not yet been sufficient characterisation or modelling to determine what the causal effect is.…”
mentioning
confidence: 99%